Phytotoxicity activities and chemical composition of the seed essential oil of Monodora myristica - Shola H. Awojide; T. Mercy Ajayi; Kehinde Adenike Oyewole; Abayomi G. Adeyemo; Olumide E. Fadunmade; E. Adeleke Adebayo; M. Tolani Abdullahi (CTU Journal of Innovation and Sustainable Development)
The phytotoxic effect of essential oil from African nutmeg (Monodora myristica) seeds on growth of tomato (Solanum lycopersicum L)., maize (Zea mays), and cowpea (Vigna unguiculata) was examined. Essential oil from the seeds of M. myristica was extracted by hydrodistillation. The essential oil’s composition was examined by gas chromatography-mass spectrometry (GC-MS). The phytotoxicity of the essential oil formulation at different concentrations for five days was evaluated on the leaves and roots. The activity was ascertained by estimating the shoots’ and the roots’ lenght. The result of GC-MS showed α–phellandrene (43.2%) as the essential oil's main constituent. The essential oil reduced the growth of the root and shoot of tomato, maize, and cowpea. At 4 mL/L treatment, the percentage inhibition of roots ranged from 63.8 to 75.4% after five days, while that of the shoot was 100% after three days. A varying toxicity was reported on the leaves of the seedlings of the plants after 24 hours. Phytotoxic was more potent on the leaves of cowpea and lowest in tomato. Phototoxic activity was also noted when essential oil was administered to the Seedling’s roots. The three species showed notable phytotoxicity when exposed to the essential oil of M. myristica.